2013
DOI: 10.1021/jp401906h
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Activity of Glucose Oxidase on Homogeneously Coated and Nanostructured Surfaces

Abstract: Protein unfolding and loss of protein function upon surface contact is a major problem in biotechnology and biomedicine. Using glucose oxidase (GOx) as a model protein, we investigated the impact of surface chemistry, topography, and confinement on enzyme activity, conformation, and affinity. A particular focus lay on the question whether the conformation of surface-bound proteins can be stabilized by embedding nanoscale adsorption sites, here in the form of monodisperse gold nanoparticles (AuNPs), into a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Moreover, GOx adsorbed on a graphene surface was hardly able to maintain the enzyme activity in a biosensor, which indicated that graphene would significantly decrease the average enzymatic activity of GOx ( Figure 3). A similar loss of enzyme activity of GOx adsorbed on nanomaterial-modified surfaces, such as CNT (Wooten et al, 2014, Goran et al, 2013 and Au NPs (Seehuber and Dahint, 2013), have also been reported previously (Table 1). …”
Section: Graphene-based Electrochemical Enzymatic Biosensors For Glucsupporting
confidence: 88%
“…Moreover, GOx adsorbed on a graphene surface was hardly able to maintain the enzyme activity in a biosensor, which indicated that graphene would significantly decrease the average enzymatic activity of GOx ( Figure 3). A similar loss of enzyme activity of GOx adsorbed on nanomaterial-modified surfaces, such as CNT (Wooten et al, 2014, Goran et al, 2013 and Au NPs (Seehuber and Dahint, 2013), have also been reported previously (Table 1). …”
Section: Graphene-based Electrochemical Enzymatic Biosensors For Glucsupporting
confidence: 88%
“…The efficiency of DET depends not only on the distance between the active site of the enzyme and the electrode but also on the properties of the electrode material and on the immobilization technique (Tellechea et al, 2012, Ludwig et al, 2013). For the limited number of GOx and GDH that are capable of DET, the efficient electron transfer still requires conformational change of the enzyme, which may result in an obvious loss of activity (Felice et al, 2013, Seehuber and Dahint, 2013). An appropriate balance between the enzymatic and electrochemical activities is vital for DET glucose biosensors, and more innovation is still necessary to reach that balance and a commercially viable product.…”
Section: The Development Of Glucose Metermentioning
confidence: 99%
“…3(d), for a sample mixed with low concentration biotin, its reactive sites on SA are mostly occupied by biotin-HRP which The saturation amount of biotin is determined by the inflection point on absorbance curve. Theoretically, an SA can bond 4 biotins, but actually an SA molecule on a CMMB bonds only 0.6 biotin while an SA on an RMMB bonds 1.6 biotin in our experiments, which may be due to SA deformation on solid surface [19][20] . Nevertheless, RMMBs show a more efficient and adequate affinity between SA and biotin than CMMBs.…”
Section: Resultsmentioning
confidence: 62%